Arabidopsis ECHIDNA protein is involved in seed coloration, protein trafficking to vacuoles, and vacuolar biogenesis - Ichino, Takuji; Maeda, Kazuki; Hara-Nishimura, Ikuko; Shimada, Tomoo (The journal of experimental botany, 2020)
An Arabidopsis thaliana mutant lacking the trans-Golgi network-localized protein ECHIDNA shows vacuole-related phenotypes, including altered seed coloration, va
Gesehen am 09.10.2020